Sequestration by IFIT1 impairs translation of 2'O-unmethylated capped RNA. - Matthias Habjan (Public Library of Science (PLoS), 2013)
Viruses that generate capped RNA lacking 2'O methylation on the first ribose are severely affected by the antiviral activity of Type I interferons. We used proteome-wide affinity purification coupled to mass spectrometry to identify human and mouse proteins specifically binding to capped RNA with different methylation states. This analysis, complemented with functional validation experiments, revealed that IFIT1 is the sole interferon-induced protein displaying higher affinity for unmethylated than for methylated capped RNA. IFIT1 tethers a species-specific protein complex consisting of other IFITs to RNA. Pulsed stable isotope labelling with amino acids in cell culture coupled to mass spectrometry as well as in vitro competition assays indicate that IFIT1 sequesters 2'O-unmethylated capped RNA and thereby impairs binding of eukaryotic translation initiation factors to 2'O-unmethylated RNA template, which results in inhibition of translation. The specificity of IFIT1 for 2'O-unmethylated RNA serves as potent antiviral mechanism against viruses lacking 2'O-methyltransferase activity and at the same time allows unperturbed progression of the antiviral program in infected cells.